ANALYZING STUDENTS' MENTAL MODEL ABOUT ACID BASE THROUGH INTERVIEW ABOUT EVENT (IAE) - Mulyani, Sri; Nurazizah, Tean; Sumarna, Omay; Wiji, Wiji; Widhiyanti, Tuszie (Jurnal Pengajaran MIPA, 2018)
Mental model plays an important role in giving reasons, describing, explaining, predicting, testing new ideas, and solving problems. Research on the mental model still needs to be done, especially regarding acid-base which is revealed by using Interview About Event (IAE). The purpose of this study was to analyze the students' mental models on the Arrhenius acid-base concept, the concept of Brӧnsted-Lowry acid base, and acid-base strength. The study was conducted on six students of class XII IPA in one high school in Bandung by using interviews that ask students to explain the given phenomenon. The answers of each student are mapped so as to derive their mental model profile. Based on the pattern obtained, there is found misconception experienced by students that all substances having atom H or OH group on chemical formula is Arrhenius acid or base, proton transfer on acid-base reaction Brӧnsted-Lowry occurs from acid to its conjugate base or from base to conjugate acid , The arrow of the reaction both in the perfect ionisation reaction and the partial ionization reaction is the same ie the arrow one (), the solute particles present in the solution in the ionizing agent are only partially ions (in the absence of molecules). Findings are useful for developing learning strategies, textbooks, media and other learning tools by linking the different levels of chemical representation to build meaning so that students' understanding is better. Keywords: acid basa, Interview About Event (IAE), misconception, mental model.AbstrakModel mental berperan penting dalam memberikan alasan, menggambarkan, menjelaskan, memprediksi, menguji ide-ide baru, dan memecahkan masalah. Penelitian mengenai model mental masih perlu dilakukan, khususnya mengenai asam-basa yang diungkap dengan menggunakan Interview About Event (IAE). Tujuan dari penelitian ini adalah untuk menganalisis model mental siswa pada konsep asam basa Arrhenius, konsep asam basa Brӧnsted-Lowry, dan kekuatan asam basa. Penelitian dilakukan terhadap enam siswa kelas XII IPA di salah satu SMA di Kota Bandung dengan menggunakan wawancara yang meminta siswa untuk menjelaskan fenomena yang diberikan. Jawaban setiap siswa dipetakan sehingga diperoleh profil model mental mereka. Berdasarkan pola yang diperoleh, ditemukan miskonsepsi yang dialami siswa yaitu semua zat yang memiliki atom H atau gugus OH pada rumus kimianya merupakan asam atau basa Arrhenius, transfer proton pada reaksi asam basa Brӧnsted-Lowry terjadi dari asam ke basa konjugatnya atau dari basa ke asam konjugatnya, tanda panah reaksi baik pada reaksi ionisasi sempurna maupun reaksi ionisasi sebagian adalah sama yaitu tanda panah satu (), partikel zat terlarut yang ada dalam larutan pada zat yang mengalami reaksi ionisasi sebagian hanya ion-ionnya saja (tanpa adanya molekul). Temuan bermanfaat untuk mengembangkan strategi pembelajaran, buku ajar, media dan perangkat pembelajaran lainnya dengan mempertautkan antar level representasi kimia untuk membangun makna sehingga pemahaman siswa menjadi lebih baik.